2022
DOI: 10.1021/acsomega.2c02751
|View full text |Cite
|
Sign up to set email alerts
|

Strain Effects on the Two-Dimensional Cr2N MXene: An Ab Initio Study

Abstract: Structural, electronic, and magnetic properties of two-dimensional Cr 2 N MXene under strain were studied. The uniaxial and biaxial strain was considered from −5 to 5%. Phonon dispersion was calculated; imaginary frequency was not found for both kinds of strain. Phonon density of states displays an interesting relation between strain and optical phonon gaps (OPGs), that it implies tunable thermal conductivity. When we apply biaxial tensile strain, the OPG increases; however, this is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…These results also show the potential applications of Cr 2 N in spintronic applications as long as they can be grown on substrates with high lattice mismatch to wake up their magnetic properties. 110 In the monolayer M 2 X MXene group (M = Hf, Ti, Nb, Sc, Ta, V, Zr. X = C, N), the magnetic moment is strongly fluctuated by the applied strain, yet the metallic characteristics remain stable under high strain loading.…”
Section: Magnetism In Mechanically Engineered Mxenesmentioning
confidence: 99%
See 1 more Smart Citation
“…These results also show the potential applications of Cr 2 N in spintronic applications as long as they can be grown on substrates with high lattice mismatch to wake up their magnetic properties. 110 In the monolayer M 2 X MXene group (M = Hf, Ti, Nb, Sc, Ta, V, Zr. X = C, N), the magnetic moment is strongly fluctuated by the applied strain, yet the metallic characteristics remain stable under high strain loading.…”
Section: Magnetism In Mechanically Engineered Mxenesmentioning
confidence: 99%
“…These results also show the potential applications of Cr 2 N in spintronic applications as long as they can be grown on substrates with high lattice mismatch to wake up their magnetic properties. 110…”
Section: Mxenes For Spintronic Applicationsmentioning
confidence: 99%
“…22,23 The strain effect is also considered to be an effective method to manipulate the electronic property and magnetocrystalline anisotropy (MCA) of 2D ferromagnetic materials. [24][25][26] For example, Sun et al…”
Section: Introductionmentioning
confidence: 99%
“…22,23 The strain effect is also considered to be an effective method to manipulate the electronic property and magnetocrystalline anisotropy (MCA) of 2D ferromagnetic materials. 24–26 For example, Sun et al theoretically reported that the MCA of single-layer (SL) Fe 2 I 2 can be effectively enhanced by applying tensile strain. 27 Likewise, it has also been demonstrated that strain can be used to manipulate the MCA in CrCl 3 , CrBr 3 , CrI 3 , and CrSI monolayer (ML).…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than 150 MAX phases formed from a combination of 14 M and 16 A elements have been reported [11]. Since 2017, researchers have synthesized about 30 new ordered MAX metal phases with double-transition-metal junctions and have studied their properties, including their magnetic [12][13][14], mechanical [15,16], electronic [17], and thermal characteristics [18]. The formation of solid solutions on M and/or X sites opens the possibility of synthesizing an infinite number of nonstoichiometric MXenes and the attractive possibility of fine-tuning the properties by mixing different transition metals or by creating carbonitrides [19].…”
Section: Introductionmentioning
confidence: 99%